If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4 + -7x = 5 + x + 13 Reorder the terms: 4 + 5x + -7x = 5 + x + 13 Combine like terms: 5x + -7x = -2x 4 + -2x = 5 + x + 13 Reorder the terms: 4 + -2x = 5 + 13 + x Combine like terms: 5 + 13 = 18 4 + -2x = 18 + x Solving 4 + -2x = 18 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + -2x + -1x = 18 + x + -1x Combine like terms: -2x + -1x = -3x 4 + -3x = 18 + x + -1x Combine like terms: x + -1x = 0 4 + -3x = 18 + 0 4 + -3x = 18 Add '-4' to each side of the equation. 4 + -4 + -3x = 18 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 18 + -4 -3x = 18 + -4 Combine like terms: 18 + -4 = 14 -3x = 14 Divide each side by '-3'. x = -4.666666667 Simplifying x = -4.666666667
| 29+2x=x+25 | | 8-3y=-4 | | 4x^3+x^3+9x^2=0 | | -102=-2(8-7r)-2 | | x-3(8)=-4 | | y=50x+90 | | 2x+27=x+21 | | 4(v+7)=6v+18 | | 31=7+3x | | (2x-5)(2x-5)-121=0 | | 8(1-2r)=-88 | | 18+x=x+23 | | 7-3a=-16 | | -2x+4=5+1x-13 | | 4x+y-47=0 | | 4u+36=6(u+4) | | 3x+1=4+x | | (2x)+x+(2x+5)=50 | | 3p^2-9p-1=0 | | 2b-67=-8n+5 | | -6n=27 | | (c+3)-(1-3c)=2 | | -5x-3=y | | 256-9x=0. | | -9(w+8)=-3w-36 | | (2x+7)(x^2+7x+8)= | | 4(3a-3)+4=35 | | -9+4n=27 | | 4x^3-3*3x^2=0 | | ?x=12 | | 3(4a-3)+4=35 | | (x)(x+5)=36 |